SUSTAINABLE MARKETING MIX – THE BASIC ASSUMPTIONS - Ewa Frąckiewicz; Edyta Rudawska; Małgorzata Wiścińska (Polityki Europejskie, Finanse i Marketing)
The growing importance of sustainable development concept finds its consequences in companies’ marketing policy, on both micro and macro level. A new concept of sustainable marketing has emerged. It focuses on the necessity of satisfying the needs with profit, while creating, communicating and delivering value for consumers, partners and the society. Therefore concentrating activities on achieving values of social, ethical and / or environmental character, while maintaining economic efficiency, marketing can be seen as an activity, which enables the implementation of sustainable development at a company level. The article fits into the current discussion on the new management concept, including marketing activities. The goal was to identify the impact of sustainable development on marketing tools of modern organizations. The article is a review and has been prepared based on an analysis of recent literature.